2022
DOI: 10.3390/jof8121310
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Citronellal can Significantly Disturb Chitin Synthesis and Cell Wall Integrity in Magnaporthe oryzae

Abstract: Background: Natural products are often favored in the study of crop pests and diseases. Previous studies have shown that citronellal has a strong inhibition effect on Magnaporthe oryzae. The objective of this study was to clarify its mechanism of action against M. oryzae. Results: Firstly, the biological activity of citronellal against M. oryzae was determined by direct and indirect methods, and the results show that citronellal had a strong inhibition effect on M. oryzae with EC50 values of 134.00 mg/L and 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(67 reference statements)
2
2
0
Order By: Relevance
“…virens was impacted by 2,4-DTBP. This phenomenon is consistent with the effects of dictamnine on Botryosphaeria dothidea, citronellal on Magnaporthe oryzae, and carvacrol on Alternaria alternata …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…virens was impacted by 2,4-DTBP. This phenomenon is consistent with the effects of dictamnine on Botryosphaeria dothidea, citronellal on Magnaporthe oryzae, and carvacrol on Alternaria alternata …”
Section: Resultssupporting
confidence: 88%
“…However, the mycelium diaphragm in the control group appeared intact, bright, and clear, while the number and fluorescence intensity of the mycelium diaphragm gradually decreased after treatment with the increasing concentrations of 2,4-DTBP, suggesting that the cell wall integrity of U. virens was impacted by 2,4-DTBP. This phenomenon is consistent with the effects of dictamnine on Botryosphaeria dothidea, 25 citronellal on Magnaporthe oryzae, 26 and carvacrol on Alternaria alternata. 27 Effects of 2,4-DTBP on Redox Homeostasis in U. virens.…”
Section: ■ Materials and Methodssupporting
confidence: 88%
“…The relative conductivity of the fruit pericarp represents the cell membrane permeability or degree of cell membrane injury, and its value increases with the degree of cell aging and damage [ 28 ]. The research results indicated that there is no difference in relative conductivity within the first 5 days of room temperature storage, a significant increase was observed starting from day 7, and the maximum value was reached at day 9, with an increase of 52.22% compared to day 0 ( Figure 4 ), indicating that the integrity of litchi fruit pericarp cell membranes can be well maintained within 5 days after harvest.…”
Section: Resultsmentioning
confidence: 99%
“…On fungi, citronellal also showed the weakest anti-fungal activity (Marei and Abdelgaleil 2018 ; Wang et al 2018 ). Citronellal showed recently to act on membrane integrity and ergosterol synthesis in the fungus Penicillium digitatum (OuYang et al 2021 ) and to disturb chitin synthesis in the fungus Magnaporthe orizae (Zhou et al 2022 ). For the oomycete Phytophthora infestans , the nature of the membrane and cell wall are different from the classical fungi with no ergosterol in the membrane and no chitin in the cell wall (Lee et al 2012 ; Wang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%